Character-Based Digital Curriculum and Learning: A Case Study in Madrasah Ibtidaiyah and Elementary Schools - Kulsum, Umi; Bahrissalim, Bahrissalim; Khadijah, Siti; Fauzan, Fauzan; Arifin, Fatkhul (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2024)
This study examines the curriculum and learning processes implemented at Madrasah Ibtidaiyah Pembangunan and Pembangunan Islamic Elementary School, focusing on integrating character values. Utilizing a qualitative research methodology, the investigation collects data through in-depth interviews, direct observations of classroom activities, and analyses of relevant documents, all aimed at gaining a deeper understanding of the educational practices at these institutions. The findings indicate that both Madrasah Ibtidaiyah Pembangunan and Bina Insani Elementary School exhibit distinctive learning characteristics that set them apart from other Islamic educational institutions. The academic policies at these schools have successfully embraced digital learning models that are closely aligned with character education. This approach effectively fosters essential character values among students, including a heightened sense of responsibility and a strong discipline regarding the appropriate use of information technology. The results suggest that the integration of digital learning with character education can substantially enhance the overall development of students within Islamic educational environments.